Unveiling solid electrolyte interface morphology and electrochemical kinetics of amorphous Sb2Se3/CNT composite anodes for ultrafast sodium storage. (January 2021) - Ihsan-Ul-Haq, Muhammad; Huang, He; Wu, Junxiong; Mubarak, Nauman; Susca, Alessandro; Luo, Zhengtang; Huang, Baoling; Kim, Jang-Kyo
Abstract: Sb2 Se3 based anodes are widely studied for advanced Na-ion batteries. However, their Na storage performance at high rates is limited to 2000 mA g −1 because of poor kinetics of redox reactions. Here, the heterointerfacial interactions taking place between Sb2 Se3 and functionalized CNTs are probed to understand the formation of Sb–O–C and Se–C bonds in the amorphous a-Sb2 Se3 /CNT composite using the density functional theory and ab-initio molecular dynamics simulations. The distinct morphologies and thicknesses of solid electrolyte interface layers formed on crystalline c-Sb2 Se3 and a-Sb2 Se3 /CNT composite electrodes are revealed by advanced cryogenic transmission electron microscopy and their influences on the kinetics of redox reactions in the corresponding electrodes are identified. The structurally robust a-Sb2 Se3 /CNT composite electrode exhibits four orders of magnitude higher Na-ion diffusion coefficient than the crystalline c-Sb2 Se3 counterpart, giving rise to an exceptional high-rate capacity of 454 mA h g −1 at 12800 mA g −1 and capacity retention of over 62% after 200 cycles at 10000 mA g −1 . The full cells containing the composite electrodes present energy and power densities of ∼175 Wh kg −1 at 0.5C and ∼5784 W kg −1 at 80C, respectively, and stable cyclic performance up to 120 cycles. Graphical abstract: Image 1 Highlights: Cryo-TEM reveals a thin and uniform SEI layer formed on the a-Sb2 Se3 /CNT anode. DFT calculations support the presence of Sb–O–C and Se–C bonds in the composite. The morphology of SEI layer is critical for kinetics of electrochemical reactions. Ultrahigh rate capability up to 12.8 A g −1 is achieved in the composite anodes. The full cell delivers an outstanding power density of ∼5784 W kg −1 at 80C.